The Transition of Young People from Study to Employment in the Light of Student Work - Novak Vesna; Žnidaršič Anja (Organizacija, 2018)
Background and Purpose: We are living in a time of accelerated globalization, which has a far-reaching impact for youth employment. Therefore, the paper presents the problem of the transition of tertiary educated young people into the working environment in terms of the importance of education and gaining work experience during their studies. The main purpose of the study was to analyze the attitudes and thinking of students regarding the selection of studies and work experience that young people are gaining during their studies with student work in connection with their job prospects.